The Missing Symbiotic Stars: A Joint Analysis with Gaia, GALEX, and XMM-Newton Data - Xiao-jie Xu; Yong Shao; Xiang-Dong Li (The Astrophysical Journal, 2024)
The existence of a population of low-accretion-rate symbiotic stars (SySts), consisting of a giant star and a compact companion (usually a white dwarf), has been proposed recently. However, their population has not been fully understood. In this work, we present an investigation on SySts candidates consisting of asymptotic giant branch stars (AGBs) by cross-correlating the Gaia DR3, the Galaxy Evolution Explorer All-Sky Imaging Survey, and the 4XMM DR13 catalogs. We first build a sample of AGBs within 500 pc based on their locations in the Gaia color–absolute magnitude diagram. We then explore the UV and X-ray properties of the sampled AGBs and compare them to known SySts and candidates. We find 10 SySts candidates based on the far-ultraviolet excess. The typical UV luminosity of the candidates is 10 ^31 erg s ^−1 , which corresponds to a typical accretion rate of 10 ^−12 –10 ^−11 M _⊙ yr ^−1 , which is more than 1 order of magnitude lower than known SySts. Based on these findings, the total number of SySts within 500 pc is estimated to be 18. The number of AGBs with X-ray flux above 10 ^−14 erg s ^−1 cm ^−2 within 500 pc is estimated to be 37. Our finding implies that a large number of low-accretion-rate SySts are yet to be detected, which provides a base for a complete understanding of their population.